Analysing of drug patterns in primary healthcare centers in Indonesia based on WHO's prescribing indicators - Elida Zairina; Inge Dhamanti; Ida Nurhaida; Davina S. Mutia; Arivazhagan Natesan (Clinical Epidemiology and Global Health)
Background: The quality of healthcare service delivery must be appropriate to detect and manage disease effectively. Nonetheless, there is a lack of data on the quality of prescribing patterns and healthcare in primary healthcare centers. Objective: This study aimed to investigate drug use patterns based on the WHO's prescribing indicators among selected primary healthcare centers in Surabaya, East Java, Indonesia. Methods: This study was cross-sectional descriptive. All prescriptions collected from patient medical records were dispensed from the outpatient pharmacy of each primary healthcare center. Data were retrospectively analyzed using WHO's prescribing indicators to measure drug use patterns. Data were entered, cleaned, and analyzed using SPSS Version 27.0. Results: About 2.21 drugs were used on average per encounter. Antibiotics and injections were prescribed in 15.7 % and 1.67 % of the encounters. The most prescribed antibiotics were amoxicillin (87 %), chloramphenicol (6.5 %), and co-trimoxazole (3 %). The percentages of drugs prescribed based on the generic name and the essential drug list were 99.6 % and 76.8 %, respectively. Antibiotic prescribing was significantly associated with patient age and the number of medications prescribed. Patients under 19 were 2.50 times more likely to be given antibiotics (COR: 2.50; 95 % CI: 1.42–4.40). Antibiotic prescribing increases by 0.38 units for each unit, increasing the number of medications prescribed (COR: 0.38; 95 % CI: 0.24–0.59). Conclusion: This study concludes that the prescribing indicators at the five primary healthcare centers in Surabaya, Indonesia differed from the WHO's standards. The antibiotic encounters, injection encounters, and the proportion of drugs prescribed based on the essential drug list were less than the WHO's standards. The study found that the percentage of prescriptions containing generic names was almost fulfilling WHO's indicators. Regulations and monitoring of medicine-prescribing practices are needed to promote rational drug use and minimize adverse drug reactions.